2018
DOI: 10.2217/pgs-2018-0142
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic Tests and Depressive Symptom Remission: A Meta-Analysis of Randomized Controlled Trials

Abstract: IntroductionBetween 30 -50% of patients with major depressive disorder (MDD) do not respond to their first antidepressant trial. Genetic variants contribute to the variance in antidepressant response rates. The clinical utility of pharmacogenetics-based decision-support tools (DSTs) is uncertain and has been the topic of much debate. ObjectivesTo conducted a systematic review and meta-analysis of prospective, randomized controlled trials (RCTs) that examined pharmacogenetic-guided decision support tools (DSTs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
130
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(151 citation statements)
references
References 43 publications
2
130
2
3
Order By: Relevance
“…Only some of the available tests were evaluated in clinical trials for potential benefits compared to standard care, and only six randomized controlled trials (RCTs) evaluating five different commercial tests are published [18][19][20][21][22][23], while dozens of different tests exist and have no published evidence from RCTs or non-randomized case control studies. The available studies, including RCTs, had some methodological limitations, for example limited sample size and imperfect blinding, but the metaanalytic evidence coming from RCTs shows that there is probably a benefit in terms of symptom remission compared to standard care, particularly in patients who did not respond to at least one previous pharmacotherapy [24]. The last key point to consider when evaluating commercial tests is which genes and genetic variants are genotyped and how the prescribing recommendations are formulated based on the genotyping results.…”
Section: Commercial Pharmacogenetic Testsmentioning
confidence: 99%
“…Only some of the available tests were evaluated in clinical trials for potential benefits compared to standard care, and only six randomized controlled trials (RCTs) evaluating five different commercial tests are published [18][19][20][21][22][23], while dozens of different tests exist and have no published evidence from RCTs or non-randomized case control studies. The available studies, including RCTs, had some methodological limitations, for example limited sample size and imperfect blinding, but the metaanalytic evidence coming from RCTs shows that there is probably a benefit in terms of symptom remission compared to standard care, particularly in patients who did not respond to at least one previous pharmacotherapy [24]. The last key point to consider when evaluating commercial tests is which genes and genetic variants are genotyped and how the prescribing recommendations are formulated based on the genotyping results.…”
Section: Commercial Pharmacogenetic Testsmentioning
confidence: 99%
“…A recent meta-analysis of five PGx DSTs tested in randomized controlled trials found a significantly higher remission rate (odds ratio: 1.7, 95% confidence interval: 1.2-2.5) among patients who received PGx-informed treatment compared to those receiving treatment as usual. 1 The utility of the PGx tests appears to be greater in patients who have failed to tolerate or respond to at least one prior medication trial. 1,2 However, recent statements from the US Food and Drug Administration and a position paper from the American Psychiatric Association have raised concerns about whether and in what circumstances clinicians should order PGx testing.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these black box tools are utilized by a considerable share of pharmacogenetic testing companies and several have been supported by randomized controlled trials in the treatment of major depressive disorder. 6 So, should we shun or should we come to terms with black box pharmacogenetic decision support tools in psychiatry?…”
mentioning
confidence: 99%